Emergence and development of the Delphi method: A scientometric perspective [Surgimiento y desarrollo del método Delphi: Una perspectiva cienciométrica] (2018)
The present work aims to characterize the development of the Delphi method, based on scientific indicators related to publications with high quality indexes. As a result of an automated search in Scopus, a database of 10341 documents recorded since 1969, has been formed. Among the main results, it is observed an exponential growth of the scientific and technical activity, related with this method. The impact of the published documents becomes verified in an ample heterogeneity of fields of the scientific knowledge. Certain invisible fact-finding schools are identified, determined by complex networks of scientific collaboration. On the other hand, some new areas and development tendencies are also explored. Although the marked variety of terminologies related to the Delphi method hinders the processing of information, it is concluded that the scientometric techniques are effective to characterize the development of this method, even beyond the perspective framework. © 2018 University of Pittsburgh. All rights reserved.